2012
DOI: 10.1101/gr.120634.111
|View full text |Cite
|
Sign up to set email alerts
|

H2B monoubiquitylation is a 5′-enriched active transcription mark and correlates with exon–intron structure in human cells

Abstract: H2B monoubiquitylation (H2Bub1), which is required for multiple methylations of both H3K4 and H3K79, has been implicated in gene expression in numerous organisms ranging from yeast to human. However, the molecular crosstalk between H2Bub1 and other modifications, especially the methylations of H3K4 and H3K79, remains unclear in vertebrates. To better understand the functional role of H2Bub1, we measured genome-wide histone modification patterns in human cells. Our results suggest that H2Bub1 has dual roles, on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
56
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 50 publications
15
56
1
Order By: Relevance
“…Huff et al (2010) showed that H2Bub1 levels decrease following the first internal exon, while Jung et al (2012) reported that H2Bub1 is mainly enriched at exon borders. Our analysis of H2Bub1 distribution in NT2 and HCT116 cells agrees with the reported reduction in H2Bub1 after the first internal exon but extends this notion by showing that exons downstream from the first internal exon are associated with stepwise drops in H2Bub1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Huff et al (2010) showed that H2Bub1 levels decrease following the first internal exon, while Jung et al (2012) reported that H2Bub1 is mainly enriched at exon borders. Our analysis of H2Bub1 distribution in NT2 and HCT116 cells agrees with the reported reduction in H2Bub1 after the first internal exon but extends this notion by showing that exons downstream from the first internal exon are associated with stepwise drops in H2Bub1.…”
Section: Discussionmentioning
confidence: 99%
“…While one study reported that H2Bub1 is significantly reduced following the first internal exon (Huff et al 2010), another study concluded that H2Bub1 is selectively enriched at exon-intron borders and proposed that this enrichment regulates the splicing of a subset of exons (Jung et al 2012).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
See 1 more Smart Citation
“…22,23 H2Bub is often enriched in the promoter region of actively transcriptional genes in both yeast and mammalian somatic cells. 18,[24][25][26] Previously, it was found that the knockout of Rad6 mammalian homolog, HR6B, results in male infertility due to defect in spermatogenesis. Detailed analysis of the knockout mice revealed that the synaptonemal complex and meiotic recombination were affected in the spermatocytes, thus strongly implicate the role of H2Bub in chromatin remodeling.…”
Section: Conserved Functions Of H2bub During Meiosismentioning
confidence: 99%
“…H2B-Ub is enriched near the 5′ end of highly expressed genes and has been implicated in transcriptional elongation, as well as chromatin structure definition (6)(7)(8)(9). Moreover, H2B-Ub directly regulates the H3K4 and H3K79 methyltransferases Set1 and Dot1, respectively (10)(11)(12)(13).…”
mentioning
confidence: 99%